Paraguay : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This paper focuses on the reform options for Paraguay's fiscal responsibilities law as well as credit growth and banking system vulnerabilities. During the first year of Paraguay's fiscal responsibility law, implementation has proven challenging, and a debate has emerged over whether its current design is excessively rigid. There are also important reputational costs to amending the framework. Paraguay has experienced rapid credit growth over the past decade. Reflecting these considerations, this chapter analyzes banks' health and potential risks in Paraguay. Paraguay's credit markets, as well as the rest of its financial system, are dominated by commercial banks.